Pelatihan Penggunaan Internet Bagi Pegawai Kantor dan Perangkat Desa Rantau Mapesai - Sahriyal Sahriyal; Erny Erny; Nedra Neswita (Universitas Pahlawan Tuanku Tambusai, 2022)
The development of the Internet makes it very easy to complete administrative work so that it requires good skills on the internet for office employees and village officials in Rantau Mempesai, Indragiri Hulu Regency, Riau Province, so training is needed. The College of Technology (STTI) lecturer team decided to hold community service (PKM) in the form of the training. The purpose of the training is to equip office employees and village officials how to complete the administration of government activities so that the administrative work process can be carried out in a very short and efficient time by searching for information, storing data and sending data. This training is carried out using lecture methods, discussions and hands-on practice with discussions on web browsing, Gmail and Geoggle drive. The results of this training evaluation showed a large increase (85.2%) of understanding for office employees and village officials in using the internet to improve skills in the field of technology.